Escherichia coli Quorum-Sensing EDF, A Peptide Generated by Novel Multiple Distinct Mechanisms and Regulated by trans-Translation - Sathish Kumar (American Society for Microbiology, 2016)
ABSTRACT Eshcerichia coli mazEF is a stress-induced toxin-antitoxin module mediating cell death and requiring a quorum-sensing (QS) extracellular death factor (EDF), the pentapeptide NNWNN. Here we uncovered several distinct molecular mechanisms involved in its generation from the zwf mRNA encoding glucose-6-phosphate dehydrogenase. In particular, we show that, under stress conditions, the endoribonuclease MazF cleaves specific ACA sites, thereby generating a leaderless zwf mRNA which is truncated 30 codons after the EDF-encoding region. Since the nascent ribosome peptide exit tunnel can accommodate up to 40 amino acids, this arrangement allows the localization of the EDF residues inside the tunnel when the ribosome is stalled at the truncation site. Moreover, ribosome stalling activates the trans-translation system, which provides a means for the involvement of ClpPX in EDF generation. Furthermore, the trans-translation is described as a regulatory system that attenuated the generation of EDF, leading to low levels of EDF in the single cell. Therefore, the threshold EDF molecule concentration required is achieved only by the whole population, as expected for QS. IMPORTANCE Bacteria communicate with one another via quorum-sensing (QS) signal molecules. QS provides a mechanism for bacteria to monitor each other’s presence and to modulate gene expression in response to population density. Previously, we added E. coli pentapeptide EDF to this list of QS molecules. We showed that, under stress conditions, the induced MazF, an endoribonuclease cleaving at ACA sites, generates EDF from zwf. Here we studied the mechanism of EDF generation and asked whether it is related to EDF density dependency. We illustrated that, under stress conditions, multiple distinct complex mechanisms are involved in EDF generation. This includes formation of leaderless truncated zwf mRNA by MazF, configuration of a length corresponding to the nascent ribosome peptide exit tunnel, rescue performed by the trans-translation system, and cleavage by ClpPX protease. trans-Translation is described as a regulatory system attenuating EDF generation and leading to low levels of EDF in the single cell, as expected for QS.